Synthesis of PdO‐ZnO mixed oxide precursors for PdZn intermetallic catalysts. Issue 9 (11th September 2014) - Paiz, Jonathan; Fitch, James; Peterson, Eric; Hough, Tyler; Barnard, Werner; Datye, Abhaya
<x xml:space="preserve">Abstract</x> Pd and Zn nitrates were aerosolized to produce droplets that were heated in air to form mixed Pd, Zn oxides. This method yields powders of uniform composition and allows study via XRD, TEM, Raman and XAS. We found that Pd+2 can be isomorphously substituted into hexagonal ZnO and Zn+2 can also be substituted within tetragonal PdO. These mixed oxides serve as precursors to form well defined PdPd‐Zn intermetallic phases. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>